Solve for x.

3x−7−2x+5=6 (1 point)
Responses

x = 7
x = 7

x = -8
x = -8

x = 8
x = 8

x = 4
x = 4
Skip to navigation

page 2 of 2

1 answer

To solve for x in the equation 3x - 7 - 2x + 5 = 6, we can combine like terms:

x - 2 = 6

Next, we can isolate x by moving the constant term to the other side of the equation:

x = 6 + 2

x = 8

Therefore, the solution is x = 8.
Similar Questions
  1. Solve Multiplication Inequalities Quick Check1 of 51 of 5 Items Question Solve 8x>24 .(1 point) Responses x<3 x less than 3 x>3
    1. answers icon 7 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. The Celsius to Fahrenheit formula: F=95C+32Solve this formula for C. Check all answers that are true. (2 points) Responses To
    1. answers icon 1 answer
more similar questions